On the diversity of the SE Indo-Pacific species of Terebellides (Annelida; Trichobranchidae), with the description of a new species - Julio Parapar; Juan Moreira; Daniel Martin (PeerJ, 2016)
The study of material collected during routine monitoring surveys dealing with oil extraction and aquaculture in waters off Myanmar (North Andaman Sea) and in the Gulf of Thailand, respectively, allowed us to analyse the taxonomy and diversity of the polychaete genus Terebellides (Annelida). Three species were found, namely Terebellides cf. woolawa, Terebellides hutchingsae spec. nov. (a new species fully described and illustrated), and Terebellides sp. (likely a new species, but with only one available specimen). The new species is characterised by the combination of some branchial (number, fusion and relative length of lobes and papillation of lamellae), and thoracic (lateral lobes and relative length of notopodia) characters and is compared with all species described or reported in the SW Indo-Pacific area, as well as with those sharing similar morphological characteristics all around the world. The taxonomic relevance of the relative length of branchial lobes and different types of ciliature in branchial lamellae for species discrimination in the genus is discussed. A key to all Terebellides species described in SE Indo-Pacific waters is presented.